Super keren 30 hari kuasai Bahasa Inggris / Badiatul Roziqin; penyunting, Dedi M. Siddiq, Ismail S.M., Fifah - BADIATUL ROZIQIN , 1980-; DEDI M. SIDDIQ; ISMAIL S.M.; FIFAH (Diva Press, 2017)
260 hlm. : ilus. ; 20 cm.